2003
DOI: 10.1074/jbc.m304368200
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar Mannitol Stimulates Expression of Aquaporins 4 and 9 through a p38 Mitogen-activated Protein Kinase-dependent Pathway in Rat Astrocytes

Abstract: The membrane pore proteins, aquaporins (AQPs), facilitate the osmotically driven passage of water and, in some instances, small solutes. Under hyperosmotic conditions, the expression of some AQPs changes, and some studies have shown that the expression of AQP1 and AQP5 is regulated by MAPKs. However, the mechanisms regulating the expression of AQP4 and AQP9 induced by hyperosmotic stress are poorly understood. In this study, we observed that hyperosmotic stress induced by mannitol increased the expression of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 56 publications
8
102
3
Order By: Relevance
“…Similar to results of the present study, p38, ERK1/2, and JNK MAPK activation by hypertonicity has been demonstrated in inner medullary collecting duct cells and in cells of the medullary thick ascending limb of Henle's loop (43)(44)(45). A role of p38, ERK and JNK in the transcriptional regulation of various aquaporins by hypertonicity has been shown in renal and lung epithelial cells and in astrocytes (45)(46)(47). Data from our present study indicate that MAPKs additionally participate in the accumulation of AQP2 at the plasma membrane, but not at the TGN, in renal CD principal cells immediately following hypertonic challenge.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to results of the present study, p38, ERK1/2, and JNK MAPK activation by hypertonicity has been demonstrated in inner medullary collecting duct cells and in cells of the medullary thick ascending limb of Henle's loop (43)(44)(45). A role of p38, ERK and JNK in the transcriptional regulation of various aquaporins by hypertonicity has been shown in renal and lung epithelial cells and in astrocytes (45)(46)(47). Data from our present study indicate that MAPKs additionally participate in the accumulation of AQP2 at the plasma membrane, but not at the TGN, in renal CD principal cells immediately following hypertonic challenge.…”
Section: Discussionsupporting
confidence: 77%
“…Although the mechanism for AQP4 upregulation in these disease states has yet to be determined, evidence from astrocyte cell culture experiments suggest that AQP4 may be upregulated by changes in extracellular osmolality (Arima et al, 2003) and hormonal factors (Gu et al, 2003). In addition, reactive astrocytosis induced by inflammatory cytokines is often associated with increased AQP4 (Badaut et al, 2003;Bloch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have shown that miR-130a functions as a transcriptional regulator of AQP4, previous reports on the promoter of AQP4 M1 suggested the presence of an E-box region that acted as a suppressor (20,28). Umenishi and Verkman (21) considered the E-box region to play a crucial role in the transcriptional suppression of the promoter.…”
Section: Mir-130a Represses Transcriptional Activity Of Aqp4 M1mentioning
confidence: 99%